2006
DOI: 10.1007/s00521-006-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the response under impact of steel armours using a multilayer perceptron

Abstract: This article puts forward the results obtained when using a neural network as an alternative to classical methods (simulation and experimental testing) in the prediction of the behaviour of steel armours against high-speed impacts. In a first phase, a number of impact cases are randomly generated, varying the values of the parameters which define the impact problem (radius, length and velocity of the projectile; thickness of the protection). After simulation of each case using a finite element code, the above-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The present research takes the work realized by Garcia et al [28,29] as a basis, which demonstrated the validity of an ANN to solve simple ballistic impact problems. The current study has generated a new set of ballistic trials with larger dimensions, and has included new environment conditions, that is, new projectile and protection characteristics, to provide a more reliable research scenario.…”
Section: Impact Scenario Parametersmentioning
confidence: 90%
“…The present research takes the work realized by Garcia et al [28,29] as a basis, which demonstrated the validity of an ANN to solve simple ballistic impact problems. The current study has generated a new set of ballistic trials with larger dimensions, and has included new environment conditions, that is, new projectile and protection characteristics, to provide a more reliable research scenario.…”
Section: Impact Scenario Parametersmentioning
confidence: 90%
“…This methodology ratifies and amplifies the conclusions obtained in the research of [22,23], extending the number of trials available and introducing new materials for the projectile and the armour. Furthermore, the different stages of the methodology bring new approaches for working efficiently in limited information scenarios, reducing the complexity of the neural model determining the minimum network architecture, and finally, performing an empirical comparison with another automatic learning classifier (SVM).…”
Section: Discussionmentioning
confidence: 52%
“…The present research takes the work realized by Garcia et al [22,23] as a basis, which demonstrated the validity of an ANN to solve simple ballistic impact problems. The current study has generated a new set of ballistic trials with larger dimensions and has included new environment conditions, that is, new projectile and protection characteristics, to provide a more reliable research scenario.…”
Section: Impact Scenario Parametersmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on 9,25 Training Algorithm Extended BackPropagation -Learning Parameters µ and η for input layer (0.7 and 1) and output layer (0.3 and 0.4)…”
Section: Use Very Small Random Initial Values (As Much As Possible)mentioning
confidence: 99%